2022
DOI: 10.3390/plants11020170
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomedicinal and Ethnobotanical Survey in the Aosta Valley Side of the Gran Paradiso National Park (Western Alps, Italy)

Abstract: Most of traditional knowledge about plants and their uses is fast disappearing because of socio-economic and land use changes. This trend is also occurring in bio-cultural refugia, such as mountain areas. New data on Traditional Ethnobotanical Knowledge (TEK) of Italian alpine regions were collected relating to three valleys (Cogne, Valsavarenche, Rhêmes) of the Gran Paradiso National Park. Extensive dialogues and semi-structured interviews with 68 native informants (30 men, 38 women; mean age 70) were carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…The rhizome has a long tradition for liqueur production and as a popular medicine, to such an extent that during the 19th century the plant was known as 'Divinum remedium' (divine remedy) [1]. Records from historical and modern ethnobotanical studies have reported a long list of popular uses of the plant [2][3][4]. More specifically, it has been employed as a stimulant, stomachic, and diuretic for rheumatic, chronic inflammatory, and musculoskeletal diseases, as well as for skin problems, typhoid fever, paralytic conditions, and delirium tremens [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rhizome has a long tradition for liqueur production and as a popular medicine, to such an extent that during the 19th century the plant was known as 'Divinum remedium' (divine remedy) [1]. Records from historical and modern ethnobotanical studies have reported a long list of popular uses of the plant [2][3][4]. More specifically, it has been employed as a stimulant, stomachic, and diuretic for rheumatic, chronic inflammatory, and musculoskeletal diseases, as well as for skin problems, typhoid fever, paralytic conditions, and delirium tremens [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The rhizome is the part of the plant officially recognized in traditional medicine, as shown by its inclusion in the European Belfrit list of botanicals [14]. Among its different uses, the rhizome is known as a remedy for superficial injuries and wounds, but a similar use of the leaves has been reported among the local population [2]. This suggests new possibilities of exploitation for medicinal purposes and a reevaluation of the leaves of this plant, which are generally discharged during rhizome harvesting for medicinal purposes.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 190 species were cited for their digestive properties, principally after drinking an infusion or decoction or after alcoholic maceration. The seeds of Foeniculum vulgare Mill., leaves of Laurus nobilis L., flowers and leaves of Rosmarinus officinalis L., and leaves of Salvia officinalis L. were the most utilized plant organs [ 14 , 60 , 73 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gentiana sp.pl. was the most representative genus utilized for this remedy ( G. acaulis L., G. dinarica Beck, G. lutea L., G. punctata L., G. verna L.) [ 14 , 23 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation